MEDICINAL PLANTS USED BY THE MANDAIS - A LITTLE KNOWN TRIBE OF BANGLADESH - Malek, Ishita; Islam, Tabibul; Hasan, Ehasanul; Akter, Shakila; Rana, Masud; Das, Protiva Rani; Samarrai, Walied; Rahmatullah, Mohammed (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
The Mandais are a little known tribe of Bangladesh inhabiting the north central regions, particularly Tangail district of Bangladesh. Their population has been estimated to be less than 10,000 people. Although the tribe has for the most part assimilated with the mainstream Bengali-speaking population, they to some extent still retain their original tribal customs, including their traditional medicinal practices. Since this practice is also on the verge of disappearance, the objective of the present study was to conduct an ethnomedicinal survey among Mandai tribal practitioners to document their use of medicinal plants for treatment of various ailments. Four traditional practitioners were found in the exclusive Mandai-inhabited village of Chokchokia in Tangail district. Information was collected from the practitioners with the help of a semi-structured questionnaire and guided field-walk method. It was observed that the four traditional practitioners used a total of 31 plants distributed into 23 families for treatment. The various ailments treated included diabetes, low semen density, jaundice, gastrointestinal tract disorders (stomach ache, indigestion, dysentery, and diarrhea), leucorrhea, pain (rheumatic pain, joint pain), skin disorders, respiratory tract disorders (coughs, mucus, and allergy), debility, fever, and helminthiasis. From the number of plants used (seven), it appeared that gastrointestinal tract disorders formed the most common ailment